Jordan : Third Review under the Extended Arrangement under the Extended Fund Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report, 2022)
Preventive actions and a robust vaccination campaign mitigated the effects of COVID-19 variants on the economy. A nascent recovery, supported by targeted fiscal and monetary measures, is underway, with real GDP growth expected at 2 percent in 2021, strengthening to 2.7 percent in 2022. However, unemployment is persisting at very high levels, particularly for the youth. Core inflation, at 0.7 percent y-o-y in September, is subdued, despite higher fuel prices, reflecting a slow pass-through, but also weak domestic demand. Reserves are comfortable, and dollarization is declining.